Terpenes in radical polymerisation: polymer synthesis and applications - Fuentes Sainz, Marina (2016)
This thesis describes novel research into the use of terpenes as monomers and controlling agents in radical polymerisation. The use of terpenes as controlling agents represents an interesting alternative to the use of synthetic, toxic and expensive additives that are most commonly used in radical polymerisation. However, there is little information in the literature about the mechanism they undergo. In this work, the first systematic study regarding the use of terpinolene and γ-terpinene as controlling agents in radical polymerisation was reported (Chapter 2). The effectiveness of these terpenes at preventing the Trommsdorff effect and regulating molecular weight and dispersity in the polymerisation of methyl methacrylate, methyl acrylate, styrene and vinyl acetate was carefully studied and their mechanism was elucidated. The development of functional renewable polymers has been gathering growing interest among the scientific community for the last decade. Terpenes are one of the most attractive alternatives to petrol-derived monomers because of their natural abundance and the presence of unsaturated moieties in their chemical structure, which offers, in theory, the possibility for polymerisation. However, a limited range of terpene-based polymers have been synthesised to date. In order to create readily polymerisable monomers, the introduction of (meth)acrylate functionalities into a range of natural terpenes was explored (Chapter 3). Initially, a two-step methodology, consisting of hydrolysis and subsequent esterification, was explored. As an alternative to the two-step protocol, allylic C-H activation catalysed by Pd(OAc)2 was also investigated as a more sustainable route to introduce a (meth)acrylate functionality into β-pinene. These synthetic protocols led to a wide range of new terpene-based monomers. In the subsequent chapter, the polymerisability of the new terpene-based monomers was evaluated (Chapter 4). The new (meth)acrylate monomers were polymerised for the first time using free radical polymerisation (FRP) techniques. A variety of new polymers showing diverse structures, from linear through to branched and crosslinked, were obtained. The polymers also exhibited a wide scope of glass transition temperatures, which allows for the tailoring of mechanical properties by changing the starting terpene. A study of the reactivity of the different functionalities in bifunctional monomers was conducted by monitoring the polymerisation via FTIR. Finally, the evaluation of carvone-based polymers as cross-linkable polymers for coating applications was conducted (Chapter 5). The carvone-based polymers were successfully coated by solvent casting or powder coating and then cured via thiol-ene chemistry. The properties of the films were carefully studied and compared to commercial acrylic coatings.